Metreleptin for metabolic disorders associated with generalized or partial lipodystrophy. Issue 3 (May 2014) - Simha, Vinaya
<x xml:space="preserve">Abstract</x> Lipodystrophy is a group of acquired and inherited disorders characterized by selective loss of adipose tissue. Despite wide genotypic and phenotypic variety, many patients with lipodystrophy have similar metabolic complications including insulin resistance, diabetes mellitus, hypertriglyceridemia and hepatic steatosis. Often, these metabolic abnormalities are severe and difficult to treat with conventional glucose and lipid-lowering therapies. Lack of adipose tissue also results in marked hypoleptinemia, and there has recently been much interest in using leptin-replacement therapy to treat the metabolic complications of lipodystrophy. Administration of metreleptin, the human recombinant leptin analogue, has been shown in prospective, open-label studies to improve glucose control, dyslipidemia and steatohepatitis. This article summarizes the current evidence for the safety and efficacy of leptin-replacement therapy in patients with lipodystrophy.